A Mini Review: Phase Regulation for Molybdenum Dichalcogenide Nanomaterials - Xiaosong Han; Zhihong Zhang; Rongming Wang (Nanomaterials, 2024)
Atomically thin two-dimensional transition metal dichalcogenides (TMDCs) have been regarded as ideal and promising nanomaterials that bring broad application prospects in extensive fields due to their ultrathin layered structure, unique electronic band structure, and multiple spatial phase configurations. TMDCs with different phase structures exhibit great diversities in physical and chemical properties. By regulating the phase structure, their properties would be modified to broaden the application fields. In this mini review, focusing on the most widely concerned molybdenum dichalcogenides (MoX2: X = S, Se, Te), we summarized their phase structures and corresponding electronic properties. Particularly, the mechanisms of phase transformation are explained, and the common methods of phase regulation or phase stabilization strategies are systematically reviewed and discussed. We hope the review could provide guidance for the phase regulation of molybdenum dichalcogenides nanomaterials, and further promote their real industrial applications.